(untitled) (Research, Society and Development, 2021)
With the agricultural activities occurrence developed in Brazil Novo municipality, Pará, in the Brazilian Amazon, the soils show degradation and compaction, deriving from the inappropriate management of this natural resource. The objective of this research was to evaluate through the data systematization of physical and chemical atributes from studies carried out, involving Permanent Preservation Areas, Pasture and Natural Regenaration, in areas with gullies presence in the Brazil Novo county – PA. Deformed and undeformed samples were collected in all the studied areas to determine the physical and chemical properties of the soil in Pasture (A – high area), Permanent Preservation Area (B – low area) and Natural Regeneration (C – intermediate area), in all points (A, B and C) land’s topography (slope) and vegetation cover was considerated. In the statistical analysis it was observed that there is no significant difference for the studied layers (0-20 and 20-40 cm), when evaluated the two studied gullies for the three areas, accepting in this way the nullity hypothesis (H0). The soils were classified as halics with low content of organic matter in Natural Regeneration areas. It is noteworthy that the isolation action of Gully 1(V1) contributed to the natural regeneration, while in Gully 2 (V2) it is necessary anthropic intervention, since it was not made any mitigation procedure from the environmental impacts promoted to the soil natural resource.